MENGGALI KONSEP KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN BUDAYA KERJA ISLAMI DI SEKOLAH DASAR - Yuliane, Yuliane; Manovtri, Reni; Rahmania, Fadilla; Marta, Alfroki (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
This research aims to explore the concept of transformational leadership in building an Islamic work culture in elementary schools. The method used in this research is a qualitative method with a literature study approach. The results of this research indicate that the principal's transformational leadership can be interpreted as a style used to influence his subordinates (teachers, administrative staff, and students) to achieve the expected educational goals. In this case, the transformational leadership of a school principal can build an Islamic work culture in elementary schools, namely a work culture that is implemented in accordance with the teachings of the Prophet Muhammad, namely Shiddiq, Istiqomah, Fathanah, Amanah, and Tabliq.